Causes and Impact of Industrial Effluents on Receiving Water Bodies: A Review - Sarwat Jahan; Ajay Singh (Malaysian Journal of Science and Advanced Technology, 2023)
Industrial development has begun to have a negative impact on the entire environment. The constant need and agreed of humans has resulted in the formation of massive polluting industries. Manufacturing, chemical and fertilizer industries are among those that are depleting the earth’s resources while also putting enormous strain on the environment and ecological system. Water pollution is well-known to be a growing problem of 21st century all over the earth. The planet’s natural diversity is affect seriously by any human activity. Rapid industrialization is an index of development of a nation, however; a rising in population growth alters it unfavorably. India, a developing nation has a challenge of maintaining a balance between these and the environment. In India, there has been a rapid growth in industrialization after freedom. The aims of this review paper represent the link between industrial effluents and define sources of water pollution present development in the research on the fresh water aquatic ecosystems.